Digital wallets usage in the Philippines determining the impact of demographics on complementarity versus substitutability - Reyes, Gianina Marie Gabrielle A.; Tenedero, Denise Manuelle D.
Digital wallets, otherwise known as e-wallets, have become more frequently used as a financial system in current times, especially during the COVID-19 pandemic. Prior to this, the Bangko Sentral ng Pilipinas (BSP) announced its target to shift 50% of retail transactions to digital transactions, and it begs the question as to whether said digital wallets are meant to replace existing financial systems such as bank accounts, or act as a complementary service to these institutions. The researchers conducted a survey with e-wallet consumers as the respondents to understand consumer insights regarding their usage of digital wallets. Descriptive statistics were used to determine how many viewed their usage of e-wallets as complements or substitutes for bank accounts, and the researchers ran a chi-square test of independence to determine whether their demographic traits had a relationship with their e-wallet usage. The results of this study found that the majority treat e-wallets as a complementary service, though many also believe that e-wallets are generally more useful than bank accounts, reflected in the attitudinal questions. Out of the demographic variables used in the model, only gender, age, and employment status had a significant relationship with an individual’s usage of e-wallets. Overall, this new financial system brought about by e-wallets should be treated as an extension of the current financial systems, serving to provide inclusivity among those who cannot access traditional banking.